Status of Pacific Black Brant Branta bernicla nigricans on Wragel Island, Russian Federation - Ward, David H; Derksen, Dirk V; Kharitonov, Sergei P; Stishov, Mikhail; Baranyuk, Vasily V (Wildfowl, 1993)
Abundance , distribution, and habitat selection of breeding and moulting Pacific Black Brant were studied on Wrangel Island in 1989-91. Two nests and <10 family flocks of Brant were found during ground searches in previously known nesting areas. The breeding population has declined from 1000-2000 pairs to probably <100 pairs. An estimated 4200 50 (Cl) moulting Brant were counted during the first aerial and photographic survey of the island in 1990. This population includes moult migrants from Alaska and mainland Russia. Most (67%) of the moulting flocks were concentrated in freshwater lakes and usually within 2 km of the coast. Lakes with low relief shorelines and adjacent preferred grasses were important habitats used by moulting birds. Breeding and moulting populations of Wrangel Island Brant are dependent on Izembek Lagoon Alaska, in autumn and disperse over the rest of eastern Pacific Flyway in winter and spring.